KEBERLANJUTAN PENGGUNAAN EMAIL MARKETING SEBAGAI STRATEGI PEMASARAN DIGITAL UNTUK UMKM: Analisis Komparatif Tools Email Marketing Sederhana dan Terjangkau untuk UMKM - Honggo, Hermawan; Lukito, Daniel; Thomas William (Applied Research in Management and Business, 2025)
Email marketing remains a promising digital marketing strategy for small businesses, especially Micro, Small, and Medium Enterprises (MSMEs), due to its cost-effectiveness and measurable impact. This study aims to analyze the sustainability of email marketing adoption by MSMEs by comparing several popular and beginner-friendly tools. Using a descriptive qualitative approach, this article presents a comparative analysis of features, ease of use, and pricing from selected tools such as MailerLite, Mailchimp, Brevo, Constant Contact, Moosend, and Flodesk. The findings indicate that each tool offers unique strengths, allowing MSMEs to choose based on their specific marketing goals and resource limitations. This paper also provides practical insights into automation, segmentation, and campaign optimization to support MSMEs in implementing email marketing strategies effectively. Ultimately, the study highlights how MSMEs can harness digital tools to enhance customer engagement and business growth through email marketing.